Contextual Considerations for Communicative Language Teaching Adoption: A Case Study of China - Alharbi, Samar (Advances in Social Sciences Research Journal, 2023)
This paper presents a summary of the main argument raised by Liao (2004) regarding the adoption of communicative language teaching (CLT) in the Chinese context. The author discusses the critical argument made by other researchers regarding CLT and emphasises the significance of considering the teaching context. The conclusion section of the research article is also summarized, highlighting the challenges associated with implementing CLT in China and the proposed solutions. The paper suggests that CLT, being a Western approach, may not be suitable for adoption in China due to the lack of contextual consideration. It further examines the difficulties faced by teachers in conducting a needs analysis and implementing the proposed context approach. The article concludes by emphasizing the need for further research and training to improve CLT practices in Chinese classrooms and raises broader questions about the applicability of these solutions in other teaching contexts, such as Saudi Arabia. The research paper addresses important issues related to CLT adoption as an education policy decision and offers potential insights for improving language teaching practices.